Perancangan Sistem Informasi Pengumuman dan Komunikasi Berbasis Web di SMK Skyhigh - Wulandari, Andini; Rahman, Mufti Fatur; Halik, Syahrul; Syukur, Pramudya Asoka (Journal of Security, Computer, Information, Embedded, Network, and Intelligence System, 2024)
The effective and efficient use of information systems is a major challenge for Skyhigh Vocational High School (SMK Skyhigh) in delivering timely and structured information to students and parents. This study aims to design and develop a web-based announcement and communication information system that can improve the accessibility and speed of information distribution within the school environment. The research employs the waterfall software development method, which includes the stages of planning, design, development, and testing. The results show that the system, built using PHP, JavaScript, HTML, and CSS, successfully meets client needs by providing an intuitive and responsive interface. Testing with both black box and white box methods indicates that all system components function well and comply with the specified requirements. In conclusion, this system offers a relevant and practical solution to communication needs at SMK Skyhigh and has the potential to be adapted by other educational institutions.